Temperature and pressure effects on GFP mutants: explaining spectral changes by molecular dynamics simulations and TD-DFT calculations. Issue 18 (22nd April 2016) - Jacchetti, Emanuela; Gabellieri, Edi; Cioni, Patrizia; Bizzarri, Ranieri; Nifosì, Riccardo
Abstract : By combining spectroscopic measurements under high pressure with molecular dynamics simulations and quantum mechanics calculations we investigate how sub-angstrom structural perturbations are able to tune protein function. Abstract : By combining spectroscopic measurements under high pressure with molecular dynamics simulations and quantum mechanics calculations we investigate how sub-angstrom structural perturbations are able to tune protein function. We monitored the variations in fluorescence output of two green fluorescent protein mutants (termed Mut2 and Mut2Y, the latter containing the key T203Y mutation) subjected to pressures up to 600 MPa, at various temperatures in the 280–320 K range. By performing 150 ns molecular dynamics simulations of the protein structures at various pressures, we evidenced subtle changes in conformation and dynamics around the light-absorbing chromophore. Such changes explain the measured spectral tuning in the case of the sizable 120 cm −1 red-shift observed for pressurized Mut2Y, but absent in Mut2. Previous work [Barstow et al., Proc. Natl. Acad. Sci. U. S. A., 2008, 105, 13362] on pressure effects on GFP also involved a T203Y mutant. On the basis of cryocooling X-ray crystallography, the pressure-induced fluorescence blue shift at low temperature (77 K) was attributed to key changes in relative conformation of the chromophore and Tyr203 phenol ring. At room temperature, however, a red shift was observed at high pressure, analogous to the one we observe in Mut2Y. Our investigation of structural variations in compressed Mut2Y also explains their result, bridging the gap between low-temperature and room-temperature high-pressure effects.